Jacques Brel traduit par Duilio Del Prete: quelques notes traductologiques - D'Andrea, Giulia (Ponti/Ponts, 2021)
This paper aims to analyse Duilio Del Prete’s vocal translations of Jacques Brel’s songs. The study focuses on the translation strategies used by the Italian singer-translator to re-create the poetic world of the Francophone artist in the two albums entitled La bassa landa (1970) and Duilio Del Prete canta Brassens (2002). Attention will also be paid to the ways in which Brel’s references to his native country are translated into Italian: in particular, we will focus on specific aspects such as the representation of the Flemish landscape, the place names and some linguistic elements rich in cultural connotations.